Sequential delivery of dual drugs with nanostructured lipid carriers for improving synergistic tumor treatment effect - Man Xu; Guangmeng Li; Haoxiang Zhang; Xiaoming Chen; Yi Li; Qianming Yao; Maobin Xie (Taylor & Francis Group, 2020)
To improve synergistic anticancer efficacy and minimize the adverse effects of chemotherapeutic drugs, temozolomide (TMZ) and curcumin (CUR) co-loaded nanostructured lipid carriers (NLCs) were prepared by microemulsion in this study. And the physicochemical properties, drug release behavior, intracellular uptake efficiency, in vitro and in vivo anticancer effects of TMZ/CUR-NLCs were evaluated. TMZ/CUR-NLCs showed enhanced inhibitory effects on glioma cells compared to single drug loaded NLCs, which may be owing to that the quickly released CUR can sensitize the cancer cells to TMZ. The inhibitory mechanism is a combination of S phase cell cycle arrest associated with induced apoptosis. Notably, TMZ/CUR-NLCs can accumulate at brain and tumor sites effectively and perform a significant synergistic anticancer effect in vivo. More importantly, the toxic effects of TMZ/CUR-NLCs on major organs and normal cells at the same therapeutic dosage were not observed. In conclusion, NLCs are promising nanocarriers for delivering dual chemotherapeutic drugs sequentially, showing potentials in the synergistic treatment of tumors while reducing adverse effects both in vitro and in vivo.